(untitled) (Journal of Scientific Research, 2020)
In this paper we have found out boundary values of degenerate configuration core of White Dwarf using Ramanujan’s method. By converting non-linear Lane Emden-type equation for degenerate core into a series using an iterative method. Considering the first five terms of the series numerical values has been calculated. The applied method is efficient and simplifies the calculation. The obtained result has been compared with exact values. Ramanujan’s method and the new iterative method are used for the first time to solve the Lane Emden equation for white dwarf core.